Precisely Tailoring and Renewing Polymers: An Efficient Strategy for Polymer Recycling. Issue 19 (21st July 2022) - Yao, Hongxin; Zuo, Yongkang; Song, Yiye; Huang, Wenyan; Jiang, Qimin; Xue, Xiaoqiang; Jiang, Li; Xu, Jinbao; Yang, Hongjun; Jiang, Bibiao
Abstract: Plastic wastes have contaminated both land and ocean environments throughout the world and hence, it is urgent to explore feasible yet cost‐effective recycling and reuse strategies for plastic wastes in order to solve this menacing problem. The so‐called "back‐to‐oligomer" chemical recycling process may be an efficient and affordable strategy to solve this global issue. However, structural control of the produced oligomers has never been achieved using this strategy until now. Here, it is reported that polymeric blends with different structures and molecular weights can be successfully tailored to homo ‐/ co ‐ oligomers with a predesigned molecular weight (MW) and an acceptable MW distribution, just by changing the feed ratio or adding a predetermined amount of alcohol. Moreover, the molecular weight of the produced oligomers can be further increased by in situ addition of the corresponding monomers into the reaction system. This recycling strategy provides an efficient method for the preparation of high‐value polymers from plastic wastes without prior sorting of mixed plastic wastes. The newly developed process through polymer chemistry and environmental engineering not only helps with the selective recycling of polyester blends, but it can also enable the recycling of polymeric mixtures composed of polyester and polycarbonate. Abstract : Here, it is reported that polymeric blends with different structures and molecular weights can be successfully tailored to oligomers with a predesigned molecular weight (MW) and an acceptable MW distribution, just by changing the feed ratio or adding a predetermined amount of alcohol.